Implementation of Hadith on Gender Towards Female Family Leaders in the PEKKA Group (Empowering Women Family Leaders) in Asahan District - Syam, Nur Fadhilah; Nurwandri, Andri (Al-Bukhari : Jurnal Ilmu Hadis, 2022)
Social life can not be separated from a leadership even to the realm of the family. Leaders in the household have been regulated by state regulations, namely KHI and Law no. 1 year 74 states that "men are heads of families and women are housewives" and is reinforced by religious arguments, one of which is QS. Annisa: 34. However, the reality is that the women are the head of the family (PEKKA) in Asahan Regency, the wives are the heads of the family while the husbands are partly unemployed, die or are seriously ill. For this reason, this research was conducted to provide a religious understanding of gender traditions to the PEKKA group, and enlightenment on other religious arguments so that they understand their rights and obligations as a wife as well as husbands who are still there to know their rights and obligations as well. This paper uses a literature review and field qualitative research, where the main objective of this research is to contribute gender traditions to female heads of household (PEKKA) that religion also provides an explanation that leaders can also be held by women with existing provisions. Men and women are also partners with the applicable rights and obligations. The author finds that some of the PEKKA groups and their husbands do not understand the gender arguments, so that there are many inequalities.